Effects of Temperature and Salinity on Seed Germination of Three Common Grass Species - Liu, Yongjie; Zhang, Shuang; De Boeck, Hans J.; Hou, Fujiang (Frontiers in Plant Science, 2021)
Temperature and salinity significantly affect seed germination, but the joint effects of temperature and salinity on seed germination are still unclear. To explore such effects, a controlled experiment was conducted, where three temperature levels (i.e. 15, 20 and 25 ℃) and five salinity levels (i.e. 0, 25, 50, 100 and 200 mmol/L) were crossed, resulting in 15 treatments (i.e. 3 temperature levels × 5 salinity levels). Three typical grass species (Festuca arundinacea, Bromus inermis and Elymus breviaristatus) were used, and twenty-five seeds of each species were sown in petri dishes under these treatments. Germination percentages and germination rates were calculated on the basis of the daily recorded germinated seed numbers of each species. Results showed that temperature and salinity significantly affected seed germination percentage and germination rate, which differed among species. Specifically, F. arundinacea had the highest germination percentage, followed by E. breviaristatus and B. inermis, with a similar pattern also found regarding the accumulated germination rate and daily germination rate. Generally, F. arundinacea was not sensitive to temperature within the range of 15-25 ℃, while the intermediate temperature level improved the germination percentage of B. inermis, and the highest temperature level benefited the germination percentage of E. breviaristatus. Moreover, F. arundinacea was also not sensitive to salinity within the range of 0-200 mmol/L, whereas high salinity levels significantly decreased the germination percentage of B. inermis and E. breviaristatus. Thus, temperature and salinity can jointly affect seed germination, but these differ among plant species. These results can improve our understanding of seed germination in saline soils in the face of climate change.